Diffusion of advanced medical imaging technology, CT, and MRI scanners, in Iran: A qualitative study of determinants. (5th October 2018) - Abedini, Zahra; Sari, Ali Akbari; Foroushani, Abbas Rahimi; Jaafaripooyan, Ebrahim
Summary: Background: Low‐income and middle‐income countries have a lot of problems in providing the financial, human, and capital resources for advanced medical imaging technologies (AMITs). Proper distribution of such expensive equipment might increase access to these services and enhance the quality and efficiency of health care. The present study aimed to identify the factors affecting the diffusion of AMITs including CT and MRI in Iran. Methods: This is a qualitative research conducted in 2017. A number of purposively chosen policy makers and managers from Ministry of Health, medical universities, hospitals, health insurance, and vendor companies were approached for face‐to‐face and semistructured interviews. Data analysis was done using thematic analysis method. Results: Three categories of influential factors were identified, including contextual, stakeholder related, and situational factors. With regards to the stakeholders, the ministry and physicians played the most important role in the diffusion process of the AMITs. Health insurance organizations and vendor companies played a minor role in distribution of the equipment. Application of political pressure by the authorities on the Ministry of Health to issue licenses for the acquisition of AMITs was taken as the most important factor and the greatest challenge in the diffusion of devices. Conclusion: The results sought to assist health system authorities to manage diffusion of AMITs effectively and assign an equitable access to the expensive resources. The diffusion management together with utilization management could largely improve efficiency and cost containment. Medical technology diffusion management de facto needs policy instruments in both supply and demand sides.